1975
DOI: 10.1111/j.1469-7998.1975.tb01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the chemical ecology of Biomphalaria glabrata: The effects of chemical conditioning by the snails kept at various densities on their growth and metabolism

Abstract: It has been shown that heterotypically conditioned media (Het. C.M.) produced by lettuce fed snails maintained at various densities can influence the allometric growth and the rates of specific growth, ingestion, egestion, assimilation and heart beat of isolated assay snails. The growth rate of the assay snails was enhanced by increasing the density of snails producing the Het. C.M. to an optimum threshold of one snail per 100 ml. Further increases in density were followed by a decline in their growth rate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In the same species trade-offs between the allocation of resources to growth versus reproduction (Ritchie et al, 1966;Thomas et al, 1975;Vernon, 1993) have been reported.…”
Section: Studies On Basommatophoramentioning
confidence: 96%
See 1 more Smart Citation
“…In the same species trade-offs between the allocation of resources to growth versus reproduction (Ritchie et al, 1966;Thomas et al, 1975;Vernon, 1993) have been reported.…”
Section: Studies On Basommatophoramentioning
confidence: 96%
“…Vernon (1995) suggested that an absence of social facilitation, caused by deprivation of social communication as a result of isolation, may play a role in reducing reproductive output of isolated B. glabrata although the substance(s) that are responsible for this observation are not known. Basommatophoran freshwater snails may release communication substances in the water that may influence feeding, growth, metabolism and reproduction in conspecifics (Ritchie et al, 1966;Thomas et al, 1974Thomas et al, , 1975. Individuals of B. glabrata are thought to be receptive to even very low concentrations of chemicals that are released by nearby conspecifics but the exact nature of these communication substances is not yet known.…”
Section: Social Facilitationmentioning
confidence: 98%
“…Growth rates decline after egg laying and are inversely proportional to oviposition rates ( P. canaliculata ; Albrecht et al ., ). Apart from direct competition for limited food resources, lower growth rates under crowded conditions may also be due to chemical suppressants, including growth suppressive chemicals such as occur in slime trails of other aquatic snails (Berrie & Visser, ; Thomas et al ., , ). The possibility that suppressive chemicals may determine apple snail growth and development in paddy fields has received little research attention.…”
Section: Density Dependence and Intraspecific Competitionmentioning
confidence: 99%
“…Les effets de la densité englobent, d'une part, les facteurs de stimulation de la croissance tels que les polypeptides, les glycoprotéines, les lipoprotéines, les acides aminés et les ionophores qui sont probablement produits par l'escargot luimême à travers les micro organismes de ses voies digestives (Thomas et al 1975). D'autre part, les effets de la densité englobent également des facteurs inhibiteurs de croissance comme l'ammoniaque, les métabolites provenant des aliments ou des fèces.…”
Section: Expression Des Résultatsunclassified